KECEMASAN PADA PASIEN DENGAN LUKA KAKI DIABETIK - Hanafi, Hanafi; Septiani, Haryati; Febrya Rahman, Ainun Najib; Harmita, Devi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
The prevalence of diabetes continues to increase from year to year in 2021. There were 90 million cases and 5.5% are predicted to have diabetic foot ulcers, and it is predicted that it will increase by 68% in 2045 with 152 million patients. This study was conducted to determine whether there was a relationship between duration of diabetes and age on the level of anxiety in patients with diabetic foot ulcers at the Kitamura clinic in Pontianak. This type of research is descriptive analytic with a cross sectional approach. The sample used in this study were 60 respondents with diabetic foot ulcers who received treatment at the Kitamura Pancasila Pontianak Clinic, the instruments used in this study were the Anxiety Inventory (S-AI) Form questionnaire to measure anxiety levels and observation sheets for respondent demographic data. The results of the Spearman Ranks test obtained with the results of significance (2-tailed) or p value = 0.005 there is a relationship between the length of time suffering from DM with anxiety levels in diabetic foot ulcers patients and there is no relationship between age and anxiety levels in diabetic foot ulcers patients with p-value 0.064. Conclusion, there was no relationship between age and anxiety level and there was a relationship between duration of DM and anxiety level in patients with DM.